THE EFFECT OF MUSIC PREFERENCE ON LEARNING OUTCOMES IN SOLFEGIO COURSES - Ichwan, Clemy Ikasari; Saputra, Dani Nur (Fakultas Ilmu Budaya, Universitas Mulawarman, 2023)
Everyone, especially students of music education study programs, of course have different musical preferences. Preference is the tendency to choose and like certain types of music. Differences in music preferences are influenced by several factors such as the level of social class, family, environment, education, and so on. Musical preferences can have an impact on musical abilities, one of which is solfegio. This study aims to determine the effect of music preference on learning outcomes of solfegio courses in music education study programs. This study uses a quantitative method to investigate the relationship between the two variables where music preference is the independent variable (X) and the learning outcomes of solfegio courses are the dependent variable (Y). Data was collected by means of interviews and questionnaires to research subjects taken at random (random sampling). The collected data was then analyzed using the SPSS 26 application to determine the correlation coefficient (r) with the product moment formula, then hypothesis testing was carried out using the t-test to obtain a positive or negative relationship between the two variables studied